2019
DOI: 10.1016/j.heliyon.2018.e01115
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of neural network training algorithms in the modeling properties of steel fiber reinforced concrete

Abstract: Our study is aimed at modeling the effect of three contributory factors, namely aspect ratio, water cement ratio and cement content on the water intake/absorption, compressive strength, flexural strength, split tensile strength and slump properties of steel fiber reinforced concrete. Artificial neural network (ANN) as a multilayer perceptron normal feed forward network was integrated to develop a predictive model for the aforementioned properties. Five training algorithms belonging to three classes: gradient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Awolusi et al [14] stated that the comparison between ANN and some classical modeling techniques such as response surface methodology (RSM), showed the supremacy of ANN as a modeling technique in analyzing non-linear relationships of data sets, which consequently provides good fitting for data and as well as better predictive ability. Karkalos et al [15] in the comparative study between regression and neural networks for modeling Al6082-T6 alloy drilling found that the MLP_ANN models were superior to the regression model, as they were able to achieve a relatively lower prediction error.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Awolusi et al [14] stated that the comparison between ANN and some classical modeling techniques such as response surface methodology (RSM), showed the supremacy of ANN as a modeling technique in analyzing non-linear relationships of data sets, which consequently provides good fitting for data and as well as better predictive ability. Karkalos et al [15] in the comparative study between regression and neural networks for modeling Al6082-T6 alloy drilling found that the MLP_ANN models were superior to the regression model, as they were able to achieve a relatively lower prediction error.…”
Section: Modelingmentioning
confidence: 99%
“…Similar to the human brain, ANNs are capable of processing multi-dimensional, non-linear, clustered and imprecise information and could be used to extract a pattern in nonlinear, complex and noisy data sets to detect the trends with high accuracy. Thus, ANN can be used to decode complicated real world problems that are sometimes challenging to evaluate using statistical approaches without the need for complicated equations, and is capable of exploring regions that are otherwise omitted when using statistical approaches [14] [34]. They are widely used by researchers to solve a variety of problems in science and engineering, forecasting, multivariate data analysis using experimental data, field observations or even incomplete or fuzzy data sets particularly for some areas where the conventional modeling methods fail such as prediction of internal combustion engine performance characteristics [35].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Pyrolysis is a popular option for thermal decomposition of biomass in the absence of oxygen. 18,19 There is no multiple training algorithms performance comparison study published for microwave pyrolysis process. 8 Biochar is a carbon rich, solid product of biomass pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, three training algorithms were compared for wind speed forecasting and performance of five training algorithms that were compared in modelling of steel fibre reinforced concrete. 18,19 There is no multiple training algorithms performance comparison study published for microwave pyrolysis process. This paper will compare the performance of 11 different training algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of Experimental values (red) with predicted values (blue). The straight line represents the linear regression[33].…”
mentioning
confidence: 99%